Effects of Different Biomass Types on Pellet Qualities and Processing Energy Consumption - Yantao Yang; Lei Song; Yuanna Li; Yilin Shen; Mei Yang; Yunbo Wang; Hesheng Zheng; Wei Qi; Tingzhou Lei (Agriculture)
This work conducts a single-factor experiment to study the effects of biomass types on the relax density, volume expansion, durability, hydrophobicity, and processing energy consumption. We analyze the differences in the quality of the pellets, and optimize the compaction conditions suitable for different biomass types including straw, hardwood, shell, and herbaceous plant. The results indicated that with a compressing force of 60~1500 N, compressing time of 10 s, powder size of less than 0.5 mm, and moisture content of 10%, the relax densities of corn straw, rice straw, selenium-rich rice straw, weigela japonica branches, and camphor leaves range from 360 to 820 kg/m3, with a processing energy consumption of 17,360 to 28,740 J/kg; meanwhile, the relax densities of argy wormwood, forage grass, green grass, and peanut shells range from 340 to 840 kg/m3, with a processing energy consumption of 33,510 to 73,700 J/kg. Therefore, the compaction pretreatment effectively regulates the density of biomass pellets and reduces the processing energy consumption. This study analyzed the differences in the quality of pellets caused by the inherent characteristics of biomass, providing strong support for the directional depolymerization and enhanced pretreatment technology for the scaled production of biomass alcohol fuels.